Prevalence of Fractures in Upper Front Incisors and its Relationship with Overjet in Costa Rica - Late Jiménez DDS, Joseph (2015)
At the present time, in Costa Rica did not exist a national research on dental trauma, an issue that has become a worldwide public health problem. The aim of this study was to determine the prevalence of traumatic dental injuries of permanent maxillary incisors. Thus, 1 626 Costa Rican school students of 12 years old were evaluated. The national prevalence of children with at least one fracture was 20.17 %, males showed a higher prevalence than women (p < 0.05). Moreover, it was observed that the group of students with more than 6 mm of overjet had a higher prevalence of fractures (p < 0.05).